2015
DOI: 10.1007/s00276-015-1489-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between petrous apex cephalocele and empty sella

Abstract: PAC is associated with empty sella, and both lesions are probably related to the same cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Previous publications reported on how impaired CSF dynamics and increased ICP could lead to herniation of meninges and CSF into the sella turcica and the petrous apex. 3,10,11 In our patient, venous disease may have played a major role in inducing intracranial hypertension, as suggested by the absence of signal in the venous sinuses on MRI. However, we think that venous obstruction may be, at least in part, secondary to distortion of the venous anatomy secondary to intracranial hypertension: Venous obstruction further increases venous pressure, CSF pressure, and ICP in a vicious cycle.…”
Section: Discussion Observationsmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous publications reported on how impaired CSF dynamics and increased ICP could lead to herniation of meninges and CSF into the sella turcica and the petrous apex. 3,10,11 In our patient, venous disease may have played a major role in inducing intracranial hypertension, as suggested by the absence of signal in the venous sinuses on MRI. However, we think that venous obstruction may be, at least in part, secondary to distortion of the venous anatomy secondary to intracranial hypertension: Venous obstruction further increases venous pressure, CSF pressure, and ICP in a vicious cycle.…”
Section: Discussion Observationsmentioning
confidence: 58%
“…Among symptomatic cases, headache, trigeminal neuralgia, CSF leak, vertigo, ataxia, facial numbness, hearing loss, diplopia, and other visual disturbances have been described. 3,6,9,10,13 Our patient was referred to us with irritability, failure to thrive, drowsiness, vomiting, and left cranial nerve VI palsy. To our knowledge, he represents the youngest patient diagnosed with CTC to date.…”
Section: Discussion Observationsmentioning
confidence: 96%
“…The association between PACs and elevated intracranial pressures is less well described; however, the previously described coexistence of PACs and empty sella supports the possible role of altered CSF dynamics in the former condition (2). Similarly, the relation between SSCD and elevated intracranial pressure is incompletely understood, but recent data demonstrate an association between obesity, OSA, and SSCD, suggesting that intracranial hypertension may also contribute to SSCD (4).…”
Section: Commentmentioning
confidence: 88%
“…Although they are usually incidental findings, they have been reported in association with cerebrospinal fluid (CSF) leaks, tinnitus, trigeminal neuralgia, vertigo, recurrent meningitis, and headaches (1). While the exact etiology remains unclear, the most widely accepted theory is that increased intracranial pressure leads to herniation of both meninges and CSF from the posterolateral portion of Meckel's cave (2). Herein, we report a unique case of an obese female patient with bilateral PACs as well as bilateral encephaloceles, superior semicircular canal dehiscence (SSCD), and empty sella.…”
mentioning
confidence: 99%
“…Several other groups have reported the radiographic incidence of PACs without reporting clinical histories (Table 2) [31][32][33] including one large study by Jamjoom and Alorainy who identified 111 PACs in 2410 brain MRIs leading to an estimate of 5.3% incidence of PACs in their cohort. [34] We describe a case of a pediatric patient with a petrous apex encephalocele leading to a CSF leak and recurrent meningitis in the setting of bilateral cochlear implantation. To our knowledge, there are no previous cases in the English literature involving a patient with a PAC and cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%